Chronical - Astra, Lilijana; Barevičiūtė, Jovilė; Jackūnas, Žibartas; Konickis, Andrius; Kowalska, W. Małgorzata; Levickaitė, Rasa; Nikiforova, Basia; Shirokanova, Anna (Creativity Studies, 2010)
“From borderline to borderland”. LIMES: Cultural Regionalistics, 3(1), p. 87-101.